Synthetic Studies on Tetracyclic Diquinane Lycopodium Alkaloids Magellanine, Magellaninone and Paniculatine - Takeru Saito; John Mark Awad; Wei Zhang (Molecules, 2023)
(–)-Magellanine, (+)-magellaninone, and (+)-paniculatine are three natural products isolated from the Lycopodium family that share a unique 6-5-5-6-fused tetracyclic diquinane core skeleton. Several members of this family have potent s anti-inflammatory and acetylcholinesterase-inhibitory properties and are under development for the treatment of Alzheimer’s and other neurodegenerative diseases. Several research groups have undertaken the formal and total syntheses of this class of natural products. This review highlights over 20 reported total syntheses of these three alkaloids and the development of synthetic methods for the assembly of their core skeletons.